PRO-ACTIVE PROPOSAL HIRING DISCRIMINATION. NEW JERSEY (Tufts Archival Research Center, 2007)
Update on the proposed New Jersey legislation that would prohibit employment discrimination due to smoking status. Lists tentative allies of the legislation, company resources, Tobacco Institute grassroots mobilization and public/media resources.